Exploratory study of threat sensitivity as a moderator of positive affect treatment and negative affect treatment for depression and anxiety. Issue 1 (28th February 2023) - Barnes-Horowitz, Nora M.; Echiverri-Cohen, Aileen; Ruiz, Julian; Zbozinek, Tomislav D.; Kim, Rebecca; Treanor, Michael; Rosenfield, David; Ritz, Thomas; Meuret, Alicia M.; Craske, Michelle G.
Cognitive behavioral therapy (CBT) focuses on decreasing negative affect rather than increasing positive affect and is ineffective for some individuals. A trial comparing novel Positive Affect Treatment (PAT) to Negative Affect Treatment (NAT; a form of CBT) showed that PAT more effectively increased positive affect and decreased negative affect, depression, and anxiety (Craske et al., 2019). The present exploratory study examined threat sensitivity as a treatment moderator. Threat sensitivity was operationalized as pre-treatment skin conductance response and unconditional stimulus (US) expectancy rating during extinction recall. Participants ( N = 43) then received 15 sessions of PAT or NAT. Growth curve models were tested to explore interactions between extinction recall and treatment condition over time. For skin conductance, weaker extinction recall predicted faster improvement in depression and anxiety in NAT than PAT, whereas stronger extinction recall predicted faster improvement in symptoms in PAT than NAT. Reduced US expectancy ratings predicted a faster decrease in symptoms, regardless of treatment condition. Individuals showing greater threat sensitivity, indexed by weaker extinction recall, may benefit more from a treatment that targets threat sensitivity than a treatment that targets reward sensitivity. Individuals showing the converse may benefit more quickly from a treatment that targets reward sensitivity than threat sensitivity.